2009
DOI: 10.1152/ajpheart.00712.2008
|View full text |Cite
|
Sign up to set email alerts
|

Antidiabetic drug pioglitazone protects the heart via activation of PPAR-γ receptors, PI3-kinase, Akt, and eNOS pathway in a rabbit model of myocardial infarction

Abstract: The insulin-sensitizing drug pioglitazone has been reported to be protective against myocardial infarction. However, its precise mechanism is unclear. Rabbits underwent 30 min of coronary occlusion followed by 48 h of reperfusion. Rabbits were assigned randomly to nine groups (n = 10 in each): the control group (fed a normal diet), pioglitazone group (fed diets containing 1 mg.kg(-1).day(-1) pioglitazone), pioglitazone + 5-hydroxydecanoic acid (HD) group [fed the pioglitazone diet + 5 mg/kg iv 5-HD, a mitochon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
35
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(39 citation statements)
references
References 27 publications
(28 reference statements)
4
35
0
Order By: Relevance
“…Pioglitazone has been reported to attenuate cardiac fibrosis and improve left ventricular failure [4][5][6]. The current study also demonstrated that pioglitazone inhibited collagen-I expression ( Figure 1C) and ameliorated cardiac fibrosis in myocardial infarction hearts ( Figure 1A and B).…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Pioglitazone has been reported to attenuate cardiac fibrosis and improve left ventricular failure [4][5][6]. The current study also demonstrated that pioglitazone inhibited collagen-I expression ( Figure 1C) and ameliorated cardiac fibrosis in myocardial infarction hearts ( Figure 1A and B).…”
Section: Discussionsupporting
confidence: 74%
“…It attenuated cardiac fibrosis, improved left ventricular failure and reduced myocardial infarct size after experimental MI [4][5][6].…”
mentioning
confidence: 99%
“…The protective role of PPAR-γ in I/R injury is suggested by data showing that heterozygous PPAR-γ-deficient mice subjected to intestinal I/R suffer more pronounced injury than wild-type control mice [6] and that the PPAR-γ agonist, rosiglitazone, is able to control cell apoptosis and contribute to tissue protection [7,8,9]. Therefore, agents that regulate PPAR-γ activation are being actively pursued.…”
Section: Introductionmentioning
confidence: 99%
“…Treatment with the antidiabetic peroxisome proliferatoractivated receptor (PPAR)-gamma agonist pioglitazone reduced myocardial infarct size, but the exact mechanism has not been elucidated. 110 Pioglitazone treatment resulted in cardiac down-regulation of miR-29a and miR-29c levels. In line, antagomirs against miR-29a or miR-29c reduced myocardial infarct size as well as apoptosis in hearts subjected to ischemia-reperfusion injury by targeting the antiapoptotic Bcl2 member Mcl-1.…”
Section: Cardiomyocytes and Fibroblastsmentioning
confidence: 99%